Projet de réaménagement de la réserve non visitable du Laténium (Suisse) - Célestine Donzé (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The archaeological deposit of the Laténium (Switzerland), which is not accessible to the public, contains archaeological material and excavation documentation. Over the years, the space has become disorganized and the capacity to provide optimal preventive conservation conditions for both these materials has been reduced. In order to restore this space’s function as a secure collections storage area, a reorganization project was launched. To structure the project and evaluate if this objective was met, a methodology was developed based on the five evaluation criteria established by Luc Rémy: « functionality, accessibility, consultation, preservation and security».